2014
DOI: 10.1186/1471-2334-14-320
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to Shiga Toxin 2 (Stx2) among Brazilian urban children with hemolytic uremic syndrome and healthy controls

Abstract: BackgroundShiga toxin (Stx)-producing Escherichia coli (STEC) infection is associated with hemolytic uremic syndrome (HUS), the main cause of acute renal failure in early childhood. Stx is essential in the pathogenesis of HUS, which has been mostly related to Stx2-producing isolates. Very limited data exist on the immune response to STEC in the Brazilian population. In this study, the prevalence of immunoglobulin G (IgG) antibodies to Stx2 was investigated in sera of children diagnosed with HUS and of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In an attempt to overcome this gap, prevalence of anti-Stx2 antibodies in sera of children diagnosed with HUS and of healthy children was recently determined 176 . The percentage of individuals showing antibodies against Stx2 was higher among HUS patients than controls, and the results also confirmed that STEC strains are circulating in our settings despite the low number of identified HUS cases.…”
Section: Enterohemorrhagic (Shiga Toxin-producing) E Coli (Ehec/stec)mentioning
confidence: 52%
“…In an attempt to overcome this gap, prevalence of anti-Stx2 antibodies in sera of children diagnosed with HUS and of healthy children was recently determined 176 . The percentage of individuals showing antibodies against Stx2 was higher among HUS patients than controls, and the results also confirmed that STEC strains are circulating in our settings despite the low number of identified HUS cases.…”
Section: Enterohemorrhagic (Shiga Toxin-producing) E Coli (Ehec/stec)mentioning
confidence: 52%
“…Similar observations were also confirmed by other investigators. Antibodies IgG to protein Stx2b were diagnosed by ELISA in 76·9% Brazilian urban children with HUS (Guirro et al 2014) and in 71% of the patients infected by an Stx2b‐producing strain (Ludwig et al 2001). In another study, conducted in Canada, 13 (93%) out of 14 paediatric patients with HUS were tested positive for Stx2b Abs (7 out of 13 were positive for both Stx1 Abs and Stx2b Abs, and 6 of the 13 were positive for Stx2b Abs only; Karmali et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, due to the importance of STEC infections in public health, HUS surveillance is compulsorily notified at a national level, and surveillance is based on a sentinel system [5]. Possible explanations on the low incidence of STEC outbreaks in Brazil is beyond the revision made by Castro et al [1], and has been explored in other publications [6,7].…”
mentioning
confidence: 99%